Dietary Sources of Plasma Trans-Fatty Acids Among Adults in the United States: NHANES 2009–2010. (29th May 2020) - Li, Chaoyang; Richter, Patricia; Cobb, Laura; Kuiper, Heather; Seymour, Jennifer; Vesper, Hubert
Abstract: Objectives: Trans-fatty acids (TFAs) increase low-density lipoprotein cholesterol, decrease high-density lipoprotein cholesterol, and increase risk of heart disease morbidity and mortality. There are two major sources from foods: industrially produced or artificial TFAs and ruminant or natural TFAs. Dietary TFA intake is estimated to cause half a million deaths annually worldwide and WHO has called for elimination of industrially produced TFAs from the global food supply by 2023. Little is known about these dietary sources for plasma TFAs. The objective of this study was to examine associations between foods consumed and plasma TFA levels using linked data of 24-hour dietary recall and plasma TFA measures among adults aged ≥20 years who participated in the NHANES 2009–2010 in the United States. Methods: Over 4400 food products in the dietary interview data were categorized into 32 food and beverage groups/subgroups. Four major plasma TFAs (palmitelaidic acid, elaidic acid, vaccenic acid, linolelaidic acid) were analyzed using gas chromatography-mass spectrometry. Multivariable regression analyses were conducted to identify associations of plasma TFAs with all 32 food and beverage groups/subgroups, controlling potential confounding effects of 11 demographic, socioeconomic, behavioral, lifestyle, and health-related risk factors. Results: Consumption of foods in the following food groups/ subgroups were positively associated with elevated plasma TFA levels: cream substitute ( P < 0.0001); cakes, cookies, and pies ( P < 0.001); milk and milk desserts ( P < 0.05); beef and lamb ( P < 0.05); and butter ( P < 0.05). Conclusions: The findings suggest that these five food groups/ subgroups could be the main dietary sources of plasma TFAs among adults in the United States in 2009–2010. Funding Sources: N/A.